L'argot de la guerre de Sarajevo, un exemple du rapport de la langue, de son lexique au vécu - Sokolija, Alma (Linguistica (Ljubljana), 2018)
Some twenty years after the war, life goes on in Sarajevo in a quasi-normal way. People are left with memories, explicit or silent. The perception of the war has not changed much. Has it evolved? It is hard to say. Rightly or wrongly the collective memory perceives and interprets certain events as acts of war and some others as treason, for the wounds are still fresh and open. The Bosnian war slang comprises euphemisms, taboos, circumlocutions and set phrases which are in many ways different from war slang in other languages, because a three-year siege is not the same as a war of the trenches. In the war in Bosnia the "others" were multiple - both enemies and traitors. This situation has generated a large number of slang expressions, which this paper tries to present on the basis of a histori-cal field study.
Keywords: argo; argot; bosanščina; bosniaque; obleganje Sarajeva; siege de Sarajevo; vocabulaire militaire; vojaško besedišče; vojni besednjak